Votive monuments from Dacia Superior in Lugosi Fodor András’ manuscript - NEMETI, Irina (Studia Universitatis Babeș-Bolyai Historia, 2016)
The present study presents two votive monuments from Dacia Superior that in the nineteenth century Lugosi Fodor András saw and documented. I have identified the items as among those depicting Mithraic and the Dolichenian iconography, I have detailed their typological identification, and have provided a brief discussion of the religious context in which they must be placed. Rezumat. Monumente votive din Dacia Superior în manuscrisul lui Lugosi Fodor András. Studiul de faţă prezintă două monumente cu caracter votiv din Dacia Superior văzute și consemnate în secolul al XIX-lea de Lugosi Fodor András. Am identificat piesele ca aparţinând iconografiei mitraice, respectiv dolicheniene și am realizat încadrarea lor tipologică, precum și o scurtă discuţie asupra contextului religios în care trebuie plasate. Cuvinte-cheie: Lugosi Fodor András, monumente votive, Dacia Superior, Mithras, Dolichenus.